2021
DOI: 10.3390/jcm10173967
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Pandemic Led to a Small Increase in Changed Mentality Regarding Infection Risk without Any Change in Willingness to Be Vaccinated in Chronic Diseases Patients

Abstract: The objective of this study was to assess the impact of the COVID-19 pandemic on patients’ perceptions regarding infection risk and vaccination in subjects suffering from chronic diseases. A prospective observational multicentric study conducted from December 2020 to April 2021 in three French University Hospitals. Patients with chronic diseases were proposed to complete a questionnaire regarding the impact of the COVID-19 pandemic on infectious risk knowledge and vaccination. A total of 1151 patients were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…This is consistent with the results of previous studies. For example, people with underlying diseases were generally less willing to be vaccinated [25][26][27][28][29][30][31][32] as they were more likely to refuse to be vaccinated due to worrying that the vaccination would aggravate their underlying diseases. This was more likely for women who were pregnant or preparing for pregnancy to refuse vaccinations, studies showed that they may hesitate to uptake the vaccine [33,34] due to the concerns about vaccine safety that large sample studies on the safety of vaccines in this group were invalid [33,35].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the results of previous studies. For example, people with underlying diseases were generally less willing to be vaccinated [25][26][27][28][29][30][31][32] as they were more likely to refuse to be vaccinated due to worrying that the vaccination would aggravate their underlying diseases. This was more likely for women who were pregnant or preparing for pregnancy to refuse vaccinations, studies showed that they may hesitate to uptake the vaccine [33,34] due to the concerns about vaccine safety that large sample studies on the safety of vaccines in this group were invalid [33,35].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some patients are either more skeptical towards vaccination against COVID more specifically or towards vaccination in general. In contrast, patients with chronic disease including chronic HF could be aware of the danger, as recently suggested [ 51 ].…”
Section: Respiratory Vaccinations From the Sars-cov2 Pandemic Perspectivementioning
confidence: 99%
“…Studies by Breuker et al, Zhou et al, and Loubet et al, have shown that individuals with chronic diseases and at risk for pneumococcal, influenza, and COVID-19 diseases have increased awareness of communicable diseases with pandemics and epidemics. The tendency of these individuals to be vaccinated against pneumococcus and influenza have increased compared to the past [ 17 , 18 , 19 ]. According to the meta-analysis in which 27 studies were included, the frequency of influenza vaccination increased with the pandemic worldwide, regardless of factors such as region, age, and sex [ 20 ].…”
Section: Discussionmentioning
confidence: 99%